Sinergi PBL dan Asistensi Pembelajaran Fisika: Upaya Akselerasi Kemampuan Pemecahan Masalah Siswa - Simangunsong, Ika Trisni; Obina, Wilfrida Mayasti; Jua, Selestina Kostaria; Nababan, Evani Doana; Uskenat, Kristina; Tonggo, Fransisco Febryan (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to enhance students’ problem-solving abilities in physics through the synergy of Problem-Based Learning (PBL) and learning assistance at SMA YPPK Yoanes XXIII Merauke. The implementation methods included: (1) socialization sessions for parents and teachers; (2) training for grade X students; and (3) mentoring for grade X students through PBL and the use of measuring instruments. The instruments used were tests validated by expert teams, while questionnaires were administered to assess parents’ understanding and students’ responses. Data were analyzed using descriptive analysis techniques. The results of this community service activity indicate that: (1) 90% of parents understood the importance of providing their children with additional lessons or tutoring; (2) students’ physics problem-solving skills improved by 77%; and (3) 14 students recognized the need for additional tutoring in physics. Overall, the program successfully strengthened students’ problem-solving abilities and increased awareness among both students and parents regarding the importance of continuous learning support.